Language Deception Tactics in PayPal Bitcoin Scam Emails: A Critical Discourse Analysis and Forensic Linguistic Approach - Eka Septi Pradani; Reno Albanire (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study investigates the deceptive language strategies employed in PayPal Bitcoin scam emails, analyzed through the frameworks of Critical Discourse Analysis (CDA) and forensic linguistics. A corpus of fifty scam emails was examined to uncover the linguistic devices used by scammers to manipulate recipients. The analysis reveals the systematic use of urgency, fear, false promises, impersonation, and credibility construction as dominant strategies in digital deception. These linguistic practices demonstrate how scammers exploit psychological vulnerabilities to gain victims’ compliance. By applying CDA, the study highlights how scam emails reproduce power asymmetries and ideologies of authority, while forensic linguistics provides insights into identifying stylistic markers of deception for investigative purposes. The findings align with and extend prior research on online fraud, phishing, and deceptive communication, offering practical implications for cybercrime prevention and victim awareness.